Washington photometry of five star clusters in the Large Magellanic Cloud - Piatti, Andres Eduardo (2009)
Aims. We present CCD photometry in the Washington system C and T1 passbands down to T1 ∼ 22.5 in the fields of NGC 1697, SL 133, NGC 1997, SL 663, and OHSC 28, five mostly unstudied star clusters in the LMC. Methods. Cluster radii were estimated from star counts in appropriate-sized boxes distributed throughout the entire observed fields. We perform a detailed analysis of the field star contamination and derive cluster colour-magnitude diagrams (CMDs). Based on the best fits of isochrones computed by the Padova group to the (T1, C − T1) CMDs, the δ(T1) index and the Standard Giant Branch procedure, we derive metallicities and ages for the five clusters. We combine our sample with clusters with ages and metallicities on a similar scale and examine relationships between position in the LMC, age and metallicity. Results. With the exception of NGC 1697 (age = 0.7 Gyr, [Fe/H] = 0.0 dex), the remaining four clusters are of intermediate-age (from 2.2 to 3.0 Gyr) and relatively metal-poor ([Fe/H] = –0.7 dex). The cluster and field age-metallicty realtions show evidence for a metallicity offset but do overlap, particularly on the upper envelope side of the cluster age-metallicity relation. Conclusions. We confirm previous results that clusters younger than ∼1 Gyr were formed during an outside-in process; this occurred after a burst of cluster formation that took place mainly in the outer disk and peaked at ∼2 Gyr ago.